BIOGAS — A SUSTAINABLE ENERGY SOURCE: NEW POSSIBILITIES AND MEASURES FOR SLOVENIA - Obrecht Matevž; Denac Matjaž (Journal of Energy Technology, 2024)
In this paper, biogas as a sustainable energy source is examined from economic, environmental and socio-politic points of view. The pros and cons of biogas and the compatibility of biogas as a sustainable energy source within EU directions and goals were examined using a SWOT analysis. Because new technologies for the exploitation of biogas are being rapidly developed and improved, technologies for the exploitation of biogas are identified, analysed and cross- compared. New possibilities, potentials and options for the development of the biogas industry in Slovenia are presented, and the possibilities for biogas exploitation and biogas potential are examined. Measures for the faster and more efficient development of biogas industry and for encouraging biogas exploitation are proposed. Proposals are also made on the basis of comparison of current state of the biogas industry in Slovenia, with current state of the biogas industry in Austria (predominantly Styria) and Sweden (predominantly Östergötland County). Proven effective measures from Austria are analysed and the implementation of the most appropriate and effective measures from Austria is proposed.